2022
DOI: 10.3389/fmicb.2022.872583
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the Gut Microbiome in the Risk Assessment of Xenobiotics and Identifying Beneficial Components for One Health

Abstract: Three areas of relevance to the gut microbiome in the context of One Health were explored; the incorporation of the microbiome in food safety risk assessment of xenobiotics; the identification and application of beneficial microbial components to various areas under One Health, and; specifically, in the context of antimicrobial resistance. Although challenging, focusing on the microbiota resilience, function and active components is critical for advancing the incorporation of microbiome data in the risk assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 75 publications
(95 reference statements)
0
22
0
Order By: Relevance
“…Since the term OH defines the holistic approach for simultaneously improving human, animal and environmental health through transdisciplinary cooperation (Bronzwaer et al., 2021 ; Buschhardt et al., 2021 ; Ampatzoglou et al., 2022 ), the human gut microbiome needs to also be included as an essential element of the NGRA approach as suggested in Figure 1 (Ortiz et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the term OH defines the holistic approach for simultaneously improving human, animal and environmental health through transdisciplinary cooperation (Bronzwaer et al., 2021 ; Buschhardt et al., 2021 ; Ampatzoglou et al., 2022 ), the human gut microbiome needs to also be included as an essential element of the NGRA approach as suggested in Figure 1 (Ortiz et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations revealed that microbiota might play an important role in xenobiotic metabolism [ 76 ]. Because of these microbiome-xenobiotic interactions, the human gut microbiota may also be a potential source of probiotics for animals and plants, and environmental bioremediation [ 77 ]. Eventually, future research will need to overcome the additional hurdle of addressing multiple biological, chemical, and physical hazards affecting multiple target organisms through multidisciplinary and holistic approaches [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Global policies necessitate going beyond the classical risk assessment for guarantying the human health through actions and implementation of the One Health approach. In this context, a new perspective is proposed for the integration of microbiome biomarkers and next generation probiotics potentially impacting and modulating not only human health, but plant, animal health and environment (Ampatzoglou et al, 2022;Ortiz et al, 2022). In this sense, the new terms established for this consortium, such as Endobolome could be proposed as part of the one health glossary that support communication and information exchange between the human health, animal health and food safety sectors (Aguilera et al, 2020).…”
Section: Impact Assessment Of the Projectmentioning
confidence: 99%